Sistem Informasi Inventory (SITORY) Berbasis Web Dengan Metode Framwork For The Application System Thinking (FAST ) - Fattya Ariani; Andi Taufik (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Inventory management must be considered in the company. Because mismanagement will result in losses in the company. UD. Berkah Jaya is a business engaged in the food and beverage trading business. Inventory management at the shop is still done manually by recording it in a ledger. This causes several problems such as unsuitable stock of goods, checking and searching for goods that take a long time, often expired stock. To solve this problem, a computerized system is needed. This study designed a web-based inventory information system (SITORY) using the FAST method. The use of the FAST method is due to rapid application development and is carried out sequentially according to the stages. This inventory system makes it easier for employees to manage inventory, to make it more efficient and accurate in reporting.